1999
DOI: 10.1021/jp9847991
|View full text |Cite
|
Sign up to set email alerts
|

Optical Constant Determination in the Infrared of Uniaxially Oriented Monolayers from Transmittance and Reflectance Measurements

Abstract: Anisotropic optical constants (index of refraction and extinction coefficient) of Langmuir−Blodgett (LB) cadmium arachidate (CdAr) monolayers have been determined from experimental FTIR spectra. The in-plane and out-of-plane complex refractive indexes were calculated using an iterative procedure from a normalized transmittance spectrum at normal incidence and a p-polarized reflectance spectrum at grazing incidence, respectively. The in-plane refractive index (n̂ x = n̂ y ) has been obtained for 8 and 10 CdA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 38 publications
4
114
0
Order By: Relevance
“…A series of the MO measurements has been performed on the basis of approximation 10. 11,13,18,24,30,31,32,[49][50][51] However, the difference between 3k iso and k max can be essential. For example, the value of 3k iso ) 0.79 characterizes bulk CdAr dispersed in KBr pellets, 49 which is distinct from the value of k max ) 1.04 found for a 11-monolayer LB film of CdAr on glass.…”
Section: Methodsmentioning
confidence: 99%
“…A series of the MO measurements has been performed on the basis of approximation 10. 11,13,18,24,30,31,32,[49][50][51] However, the difference between 3k iso and k max can be essential. For example, the value of 3k iso ) 0.79 characterizes bulk CdAr dispersed in KBr pellets, 49 which is distinct from the value of k max ) 1.04 found for a 11-monolayer LB film of CdAr on glass.…”
Section: Methodsmentioning
confidence: 99%
“…These spectral modifications can be explained from simulation of PM-IRRAS spectra using a program developed in the L.P.C.M laboratory. 27 Indeed, a slight modification of the isotropic extinction coefficient of the v as (Si-O-Si) mode ͑with k Ќ уk ʈ ) on a thickness of about 0.5 m allows us to reproduce the signal modification observed for poled surfaces in the 1000-1100 cm Ϫ1 spectral range ͑Fig. 11͒.…”
Section: B Ftir Spectroscopymentioning
confidence: 92%
“…Yamamoto and Ishida [115,142] extended Hansen's method to the case of biaxial anisotropy. Based on the matrix method of Ohta and Ishida [134] and the generalization of Yamamoto and Ishida [115,142], Buffeteau et al [143] suggested the computation procedure applicable for an arbitrary succession of coherent anisotropic and incoherent layers.…”
Section: Input Mediummentioning
confidence: 99%